Koninginins L and M, two polyketides from Trichoderma koningii 8662. (March 2015) - Lang, Ba-Yi; Li, Jing; Zhou, Xiao-Xue; Chen, Yu-Hui; Yang, Yin-He; Li, Xiao-Nian; Zeng, Ying; Zhao, Pei-Ji
Graphical abstract: Highlights: Two novel metabolites named koninginins L and M were isolated from Trichoderma neokongii 8662. Two new structures were elucidated by 1D-, 2D-NMR, HR-EI-MS, and X-ray experiments. Compounds1 –5 were assayed for nematicidal activity, and compound 3 had weak activity. Abstract: Two new fungal metabolites, named koninginins L (1 ) and M (2 ), together with three known koninginins A (3 ), E (4 ), and trichodermaketone C (5 ), were isolated from solid fermentation products of Trichoderma koningii 8662. Koninginins L (1 ) and M (2 ) were elucidated by extensive spectroscopic methods, including 1D and 2D NMR, HR-EI-MS experiments, and the absolute configuration of compound1 was confirmed by single-crystal X-ray diffraction analysis using the anomalous scattering of Cu Kα radiation.